New Trends in Image Analysis and Processing, ICIAP 2013 Workshops Naples, Italy, September 2013, Proceedings - Petrosino, Alfredo; Maddalena, Lucia; Pala, Pietro; Cantoni, Virginio; Ceccarelli, Michele; Murphy, Robert F.; Del Bimbo, Alberto; Pantic, Maja.; Grana, Costantino; Oomen, Johan; Serra, Giuseppe; Leo, Marco; et al. (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the refereed proceedings of the workshops held with the 17th International Conference on Image Analysis and Processing, ICIAP 2013, held in Naples, Italy, in September 2013. The proceedings include papers from the five individual workshops focusing on topics of interest to the pattern recognition, image analysis, and computer vision communities, exploring emergent research directions or spotlight cross-disciplinary links with related fields and / or application areas.
Pattern recognition -- Image analysis -- Computer vision.- Links with related fields and / or application areas.
Keywords: Pattern recognition; Artificial intelligence; Optical data processing; Computers and civilization; Pattern Recognition; Artificial Intelligence; Image Processing and Computer Vision; Computers and Society